Current Problems of Concluding an Agreement on the Alimony Payment for Minors in Russia - ARTEMYEVA, Yulia; IVANOVSKAYA, Natalya; KONCHEVA, Valentina; SITKAREVA, Elena (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505/jarle.v9.3(33).08, 2018)
The purpose of the manuscript is to analyze the trends and peculiarities of contractual regulation of alimony obligations concerning minors in Russia. The authors use a set of philosophical, general and special scientific methods of cognition of theoretical and empirical materials. In the course of the research, a dialectical-materialistic method was used to study the norms of family and civil law in their interrelations, interdependence, contradictions, taking into account all-roundness and objectivity in the study. In order to conduct a comprehensive study of problematic issues, general scientific methods (analysis, synthesis, deduction, induction, systemic) and private-science (comparative-legal, formal-legal, technical-legal, social modeling of the research) methods of cognition are used in the manuscript. The proposed comparative legal study allows for determining the main directions for the following: comprehensive improvement of the legal norms for the protection of the interests of the child in the process of divorcing parents, establishing the subject composition of agreements on the payment of alimony, determining the criteria for taking into account the various factors of participation in the life of the child when calculating the amount of content, developing a system of extra-judicial resolution of material welfare issues of the child during divorce, to optimize judicial practice, create a comfortable atmosphere for the development and upbringing of children.